Chipinge Town Council Building Inspection System - Tambudzayi, Nomatter (Midlands State University, 2017)
Chipinge Town Council Building Inspection system is an online software that manages, queries and inspection of stands to the Chipinge residents. The system allow clients to book, request for inspection, receiving the response online whilst the housing director is able to assign Inspectors tasks and there is generally improvement on the interaction between the clients and the Town Council through online communication that is facilitated by sending and receiving queries. The system was developed as a result of problems that were associated with the old system which were, the problem of lost clients’ information due to mismanagement of files, lack of transparency and manipulation of clients’ information by unscrupulous employees, long queues of clients who want to book for inspection and also bribery was rampant among the building inspectors. After evaluation of several alternatives in solving these problems, In-house development was agreed by the developing team in delivering the new system. Feasibility study in form of technical, economic and social was done which proved economically viable to develop this system. The research instruments to gather information which were used included interviews, questionnaires and observation and they were used on Housing Director, Inspectors and clients respectively. The system was developed using PHP, XAMPP, JavaScript and MySQL. Testing was done through validation and verification which was successful. The implementation process was done using the direct changeover because of its minimum costs. Adaptive maintenance was chosen because the system is always evolving and it needs to meet the technological changes. An aftermath implementation review was done it was noted that there was great improvement on service delivery at Chipinge Town Council as the feedback that was obtained revealed that the users were being satisfied by the system and liked the system. Though the system has received much applaud there are some future work which have been put forward regarding the system which are as follows; In future, the system will introduce the stand application system to work hand in hand with this system. The system will cater for all mobile banking facilities that are Ecocash, One-wallet or Telecash, as well as internet banking to make it easier for the clients to pay for inspection booking.